Reading My Father’s Leggìo: An Autotopography of Mourning in Translation - Basile, Elena (Italian Canadiana)

(untitled) (Iter Press, 2024)
This essay is part of a wider project of autoethnographic exploration of the memory- and place-making function that keepsake objects perform in the context of the multi-scalar and more-than-human temporalities of colonial modernity and its pervasive geographies of displacement. In it, I engage in quiet conversations with an object associated with my father’s life, illness, and death in Bari, Italy – a wooden bookstand, or leggìo, which my father made out of repurposed wood. For over twenty years, this leggìo actively interacted with my spaces of migrant dwelling, affectively modulating my discomfited sense of hyphenated belonging among urban domestic interiors in Canada – at times attenuating my internal displacements and longings and at others amplifying them. This essay converses with the strange animacy accrued by the leggìo over the decades, at first just triggering my own personal memory work, but then moving outward into more difficult and demanding ethical questions about environmental stewardship and decolonial futurity, once I start interrogating the object’s material components and their manufactured provenance.